Estudo dos parâmetros e mecanismos de cristalização de vidros e vitrocerâmicas aluminosilicato de cálcio dopados com Nd³+ - Muniz, Robson Ferrari (2012)
For many years, the Photothermal Phenomena Group (GEFF) of the Physics Department (DFI) of Maringá State University (UEM) has been making effective the obtaining of Aluminosilicate Glasses. Over these years, a lot of works was produced in order to present results achieved in this field. However, the process of nucleation and crystal growth of vitreous systems weren't accurately investigated. Hence, the aim of this dissertation has two sides. On the one hand, to analyze the mechanisms and parameters of crystallization in the syntheses of Calcium Aluminosilicates glasses. The other, to get transparent glass-ceramics by means of controlled crystallization of the precursors glasses CAS and LSCAS through a scheduled heat-treatment. In this work, were prepared and characterized a number of four samples of the glassy systems CaO-Al2O3-SiO2-MgO. In addition to examining the behavior of the samples in relation to heat-treatments, whenever as possible, the data obtained for CAS glasses were compared with the LSCAS, in order to check the changes in the properties studied. Although the main study was based on the results of thermal analysis, other techniques (X-Ray Diffraction, Absorption and Emission Spectroscopy, Confocal Raman Microscopy) were used in order to obtain additional information about the effect of heat-treatments on these samples. The results showed that in this glass system the surface crystallization was more favorable than the bulk (internal), which generally need nucleating agent. In the CAS matrix the ion of neodymium acted as a facilitator of crystallization. The data from differential thermal analysis allowed the determination of the characteristic transition temperatures (Tg, Tx and Tp) and the determination of the activation energy (E) of the samples, very important parameter in the study of the nucleation process. Two methods were applied for determining the temperature at which the nucleation rate is maximal. By confocal Raman microscopy it was estimated that the crystallized region is 20-30μm. Finally, this dissertation presents an extensive bibliography for who wishes to begin studies on the crystallization of glassy systems.